Ultrafast optical spectroscopy of the lowest energy excitations in the Mott insulator compound YVO 3: Evidence for Hubbard-type excitons - Novelli, Fabio; Fausti, Daniele; Reul, Julia; Cilento, Federico; Van Loosdrecht, Paul H. M.; Nugroho, Agung A.; Palstra, Thomas T. M.; Grueninger, Markus; Parmigiani, Fulvio (Physical Review B - Condensed Matter and Materials Physics, 2012)
Revealing the nature of charge excitations in strongly correlated electron systems is crucial to understanding their exotic properties. Here we use broadband ultrafast pump-probe spectroscopy in the visible range to study low-energy transitions across the Mott-Hubbard gap in the orbitally ordered insulator YVO 3. Separating thermal and nonthermal contributions to the optical transients, we show that the total spectral weight of the two lowest peaks is conserved, demonstrating that both excitations correspond to the same multiplet. The pump-induced transfer of spectral weight between the two peaks reveals that the low-energy one is a Hubbard exciton, i.e., a resonance or a nearly bound state between a doublon and a holon. Finally, we speculate that the pump-driven spin disorder can be used to quantify the kinetic energy gain of the excitons in a ferromagnetic environment. © 2012 American Physical Society.
CRIS-Team Scopus Importer:2022-07-20